2020
DOI: 10.3892/etm.2020.9234
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of γ‑globulin combined with dexamethasone and methylprednisolone, respectively, in the treatment of acute transverse myelitis and its effects on immune function and quality of life

Abstract: Effects of γ-globulin combined with dexamethasone or methylprednisolone in the treatment of acute transverse myelitis (ATM) were investigated. A retrospective analysis of medical records from 136 ATM patients admitted to Linzi District People's Hospital from July 2014 to September 2017 was performed. Patients treated with dexamethasone combined with γ-globulin were in group A (66 cases), and patients treated with methylprednisolone combined with γ-globulin were in group B (70 cases). Clinical efficacy, recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Quality of Life Assessment. At discharge, the 36-Item Short-Form Health Survey (SF-36) [26] was used to evaluate the quality of life of patients from the dimensions of cognitive function, body function, role function, social function, and emotional function, with a score of 100. The higher the score, the better the quality of life.…”
Section: Comparison Of Inflammatory Factorsmentioning
confidence: 75%
“…Quality of Life Assessment. At discharge, the 36-Item Short-Form Health Survey (SF-36) [26] was used to evaluate the quality of life of patients from the dimensions of cognitive function, body function, role function, social function, and emotional function, with a score of 100. The higher the score, the better the quality of life.…”
Section: Comparison Of Inflammatory Factorsmentioning
confidence: 75%
“…Therefore, it is important for the RSA group to quit smoking and alcohol during pregnancy preparation, otherwise it will have a serious negative impact on the normal development of the fetus. [16] ③To improve self-awareness: Many patients have a low level of awareness about recurrent spontaneous abortion. Medical staff can also explain the causes of the disease, treatment methods, and related precautions and contraindications during treatment to patients to improve their understanding of the disease, and assist in improving their treatment compliance and efficacy [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids protect spinal cord function by inhibiting neuroinflammation related to spinal cord injury and preventing a systemic immune response ( Chio et al., 2021 ). Studies ( Wang et al., 2020 ) have demonstrated that the utilization of corticosteroids can elevate the likelihood of experiencing adverse drug reactions. Ganglioside (GM) predominantly resides within the brain tissues of all mammals and serves as a structural constituent of human nerve cell membranes ( Yuki, 2001 ).…”
Section: Discussmentioning
confidence: 99%